Long-Term Changes in the Abundance of Benthic Foraging Birds in a Restored Wetland - Mander, Lucas; Scapin, Luca; Thaxter, Chris B.; Forster, Rodney M.; Burton, Niall H. K. (Frontiers in Ecology and Evolution, 2021)
Estuaries have historically been subject to considerable habitat loss, and continue to be so where the natural landward migration of intertidal habitats is constrained by hard coastal defences. Where direct (e.g. port development) or indirect (e.g. sea-level rise) processes are predicted to threaten intertidal habitats and associated waterbird species, there is a regulatory requirement to produce compensatory intertidal habitats. Managed realignment (MR) is a shoreline management practice that is undertaken to build sustainable coastal defences as well creating intertidal habitats in estuaries. This nature-based solution brings multiple benefits in the form of carbon storage, increased resilience to flooding and potentially, the formation of new habitat, which is the topic of this study. A 75-hectare site at the Paull Holme Strays (Humber Estuary, UK) was monitored over a 10-year period following managed realignment to examine the change of abundance of waterbirds in response to the physical processes occurring there. Using Digital Terrain Models (DTM) collected via Light Detection and Ranging (LiDAR), we examined how four compensatory target species responded to changes in elevation after the site’s creation. We show that the very rapid accretion of estuarine sediment occurred in the first decade of the new re-created intertidal, which led to changes over time in the numbers of benthic foraging birds supported. Elevation change was driven by sediment accretion, the rate of which depended upon the initial bed elevation of sectors within the site. Ten years after the habitat re-creation, there was still a high spatial heterogeneity in bed elevation; however, sectors with the lowest elevation accreted the most over a 10-year period. The foraging numbers of four waterbird species that colonised the MR site significantly declined above a certain elevation, with this effect being most pronounced for Eurasian Curlew (Numenius arquata). Numbers of Common Shelduck (Tadorna tadorna), Dunlin (Calidris alpina) and Common Redshank (Tringa totanus) declined significantly after initial peaks 5 to 7 years after the site’s creation, reflecting the on-going elevation changes.